Measuring Local Tourists’ Perceptions in Petra City as One of Seven Wonders of World - AL NAJDAWI, Bashar M.; KHALEEFAH, Qusay Q.; SHATNAWI, Hakam S.; AL MOMANI, Emran M. (Journal of Environmental Management and Tourism, 2017)
The purpose of study is to investigate the influence of the independent factors on the tourist's satisfaction for providing services in the tourist's destination in the city of Petra as a tourist's attraction. Questionnaires were distributed to local tourists’ who is visit Petra city. Of the 600 distributed, 568 usable questionnaires were retrieved. A judgmental sampling approach was used. The principal finding is Accommodation, Restaurant, Eco- awareness, and Transportation , have a significant positive effect on tourists' perception . Moreover, the factors (Accommodation, Restaurant, Eco- awareness, and Transportation) are significant because sig.<0.05 and there is a relationship between these factors and tourist perceptions because the significant value is less than 0.05; thus, all the hypotheses are accepted. This study is significant and useful for many reasons. Firstly, it investigates the possible impacts of the degree of satisfaction of local tourists for services provided in the tourist attractions. Secondly, the perceptions of local tourists from the tourist's destination. Finally, the study provides some propositions and managerial implications regarding to the Petra Development and Tourism Authority to develop their services and raise the quality to reach the tourists' satisfaction among domestic tourists'.